Analisis Kelayakan Usaha Peternakan Sapi Perah Di Desa Ngabab Kecamatan Pujon Kabupaten Malang - M. Rizal Amri Chusen; Parikesit Penangsang (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to analyze the acceptance, profit and feasibility of diary farming in Ngabab Village, Pujon District, Malang Regency. In this study, 6 dairy farm owners in Ngabab Village, Pujon District, Malang Regency were used as informants. This research uses descriptive qualitative research. Data was collected through interviews, and the analytical methods used in this research were fixed costs, variable costs, total costs, revenues, profits and business feasibility in this research using the calculation of Revenue Cost Ratio (R/C), Benefit Cost Ratio (B/C), and Return On Investment (ROI). The results obtained from this research were by using calculations of Revenue Cost Ratio (R/C), Benefit Cost Ratio (B/C), and Return On Investment (ROI), resulting in high numbers obtained in R/C Ratio, B/C Ratio, and ROI exceed the figures or values that have been determined so that it can be concluded that based on the calculation results the dairy farming busuness in Ngabab Village, Pujon District, Malang Regency is worthy of cultivation and development.